2015
DOI: 10.1161/circoutcomes.115.001483
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ and Providers’ Perspectives of a Polypill Strategy to Improve Cardiovascular Prevention in Australian Primary Health Care

Abstract: Background-This study explores health provider and patient attitudes toward the use of a cardiovascular polypill as a health service strategy to improve cardiovascular prevention. Methods and Results-In-depth, semistructured interviews (n=94) were conducted with health providers and patients from Australian general practice, Aboriginal community-controlled and government-run Indigenous Health Services participating in a pragmatic randomized controlled trial evaluating a polypill-based strategy for high-risk pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 40 publications
1
24
1
Order By: Relevance
“…While a polypill was acceptable to most patients of the UMPIRE trial, some felt that FDC therapy was less tailored to individual patient needs. 49 A recent investigation of the views of cardiovascular patients and providers who participated in polypill trials reported similar advantages and concerns to those identified in our study, 50 suggesting that polypill perspectives translate to other regions and healthcare settings.…”
Section: Discussionsupporting
confidence: 78%
“…While a polypill was acceptable to most patients of the UMPIRE trial, some felt that FDC therapy was less tailored to individual patient needs. 49 A recent investigation of the views of cardiovascular patients and providers who participated in polypill trials reported similar advantages and concerns to those identified in our study, 50 suggesting that polypill perspectives translate to other regions and healthcare settings.…”
Section: Discussionsupporting
confidence: 78%
“…In 2019, the PolyIran trial demonstrated that the combination of aspirin, atorvastatin, and either lisinopril or valsartan led to a 34% lower risk (95% CI 20-45%) for cardiovascular events compared with usual care over 5 years when implemented in a large, cluster-randomized trial across 236 villages (n = 6,838 participants) in Iran [10]. These results contrasted with the Kanyini-GAP polypill trial in Australia (n = 623 participants), where there were no significant differences in changes in risk factors nor clinical outcomes between groups over 18 months despite a 49% (95% CI 30-72%) higher relative rate of self-reported adherence to indicated therapy among individuals randomised to aspirin, simvastatin, lisinopril, and either atenolol or hydrochlorothiazide compared with usual care [11]. Differences in outcomes between these trials may be due to differences in the respective comparator groups, i.e.…”
Section: Fixed-dose Combination Therapy For Cardiovascular Disease Prcontrasting
confidence: 59%
“…Regarding the costs of treatment with the polypill for primary and secondary CVD prevention, several studies have shown that the cost benefits of polypill use were significantly lower than the use of component drugs given separately. In addition, the patient and doctor acceptance of the polypill were significantly higher compared with the component drugs given separately . .…”
Section: Clinical Evidence Demonstrating the Importance Of Crf Modifimentioning
confidence: 90%
“…In addition, no problems have been found between the component drugs of the polypill regarding bioavailability and pharmacokinetic interactions . With respect to the effectiveness and costs of the polypill, these have been shown to be highly acceptable by patients and doctors alike . In fact, the polypill has been called “a best bargain” for the primary and secondary prevention of CVD and strokes.…”
Section: Possible Composition Of the Polypillmentioning
confidence: 99%
See 1 more Smart Citation